Wear-resistant PET (Polyethylene Terephthalate) bottle and preparation process thereof

By using modified ceramic powder and glass fiber in PET materials, the problem of easy wear of PET materials during friction and scratching is solved, the wear resistance and mechanical properties of the material are improved, the service life is extended, and the service life is improved Processing performance.

CN119432017AActive Publication Date: 2025-02-14FOSHAN HUAXIN HENGFENG POLYESTERIFCATION PACKAGING CO LTD

Patent Information

Application Number
CN202411560262.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

PET materials are prone to scratches or wear during friction and scratching, which affects their durability and service life. The interface compatibility between filler particles and polymer materials is poor, affecting the overall performance of the material.

Method used

Modified ceramic powder and glass fiber are used to modify the ceramic powder through titanate coupling agent to increase its compatibility with PET resin, so that the ceramic powder is evenly filled with PET resin, and then the ceramic powder is compounded through B2O3-A12O3. The combination of phase powder and nano-alumina improves the dispersion and interface compatibility of the powder.

Benefits of technology

Improves the wear resistance and mechanical properties of PET materials, reduces the risk of wear and damage, extends the service life of the material, and improves processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117696720000081
    Figure BDA0005117696720000081
Patent Text Reader

Abstract

The invention relates to the technical field of PET materials, and particularly discloses a wear-resistant PET bottle and a preparation process thereof. The wear-resistant PET bottle is prepared from the following raw materials: PET resin, modified ceramic powder, glass fibers, a flexibilizer, an antioxidant, a light stabilizer and a lubricant. Wherein the modified ceramic powder comprises B2O3-Al2O3 complex-phase powder and a titanate coupling agent, the B2O3-Al2O3 complex-phase powder is modified by the titanate coupling agent, one end of a coupling agent molecule is connected with B2O3-Al2O3 complex-phase powder particles through chemical action, and the other end of the coupling agent molecule is crosslinked with PET resin, so that the compatibility of the ceramic powder and matrix resin is improved; and the ceramic powder is uniformly dispersed in the PET resin, so that the wear resistance of the PET resin is effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PET materials, and in particular to a wear-resistant PET bottle and a preparation process thereof. Background Art

[0002] In the packaging field, PET plastic bottles have become one of the most widely used packaging materials due to their light weight, transparency, and easy recycling. PET plastic bottles are not only widely used in the packaging of beverages such as carbonated drinks, drinking water, juice, enzymes, and tea drinks, but also widely used in other packaging fields such as food, chemicals, and medicines. PET plastic bottles have many advantages, such as low production cost, chemical resistance, and easy processing and molding.

[0003] However, the PET material itself has certain deficiencies in terms of wear resistance. In daily use, PET plastic bottles often encounter friction and scratches, which may cause scratches or wear on the bottle surface, affecting its appearance and service life. Therefore, in order to improve the wear resistance of PET plastics, various fillers are usually added to the PET material to enhance the wear resistance of the material. For example, inorganic fillers such as calcium carbonate, talcum powder, and wollastonite powder, as well as organic fillers such as carbon fiber and glass fiber. These fillers can increase the hardness and rigidity of the PET material, thereby improving the wear resistance. However, these methods also bring some new problems. The interface compatibility between the filler particles and the polymer material is poor, and due to the small particle size of the filler particles, self-agglomeration is prone to occur, thereby affecting the comprehensive performance of the material. Summary of the invention

[0004] In order to improve the dispersibility of filler particles and the interface compatibility with the matrix resin and enhance the wear resistance of PET materials, the present application provides a wear-resistant PET bottle and a preparation process.

[0005] In the first aspect, the present application provides a wear-resistant PET bottle, which adopts the following technical solution: A wear-resistant PET bottle is prepared from the following raw materials in parts by weight: PET resin 60-70 parts; 4-8 parts of modified ceramic powder; Glass fiber 8-12 parts; 1-3 parts of toughening agent; Antioxidant 0.1-0.3 parts; Light stabilizer 0.3-0.5 parts; Lubricant 0.4-0.6 parts; The modified ceramic powder is prepared from B2O3-A12O3 composite powder and titanate coupling agent, and the weight ratio of the B2O3-A12O3 composite powder to the titanate coupling agent is 10:(0.5-0.7).

[0006] By adopting the above technical scheme, PET resin is used as the matrix resin, and the ceramic powder is modified by a titanate coupling agent. One end of the coupling agent molecule is connected to the B2O3-A12O3 composite powder particles through chemical action, and the other end is cross-linked with the PET resin to increase the compatibility of the ceramic powder with the matrix resin, so that the ceramic powder is uniformly filled with the PET resin. Since the B2O3-A12O3 composite powder is small in size, it can be evenly dispersed in the matrix resin. During the friction process, on the one hand, the powder particles that are debonded when the material surface is worn have strong surface activity and are easy to combine with the dual surface to form a fine thin layer, thereby forming a boundary lubrication film on the friction surface. On the other hand, it can produce enrichment on the polymer wear surface, and the amount of powder particles re-embedded in the polymer matrix almost reaches the extent of covering the entire wear surface, forming a complete lubrication film on the polymer surface, so that the possibility of direct wear of the PET resin matrix is ​​reduced, thereby improving the overall wear resistance of the material. In addition, the addition of glass fiber can further improve the crystallization performance and mechanical properties of the PET material.

[0007] Preferably, the B2O3-A12O3 composite powder is prepared from micron boron oxide and nano alumina, and the weight ratio of the micron boron oxide to the nano alumina is 1:(1.8-2.2).

[0008] By adopting the above technical solution, due to the inertness of the chemical reaction of boron oxide, it cannot form a chemical bond with the functional group in the titanate coupling agent. Therefore, boron oxide and aluminum oxide are prepared into a composite powder, and nano-alumina is used as an intermediary. By modifying the aluminum oxide, the surface of the composite ceramic powder is connected with the coupling agent molecules, so that it can react with the matrix resin. In addition, the nano-alumina is relatively evenly dispersed around the micron boron oxide particles, rather than in a state of agglomeration, and the agglomeration phenomenon is not obvious. The nano-alumina forms a certain bonding and coating effect on the micron boron oxide, so that the composite ceramic powder has a good phase.

[0009] Preferably, the titanate coupling agent includes at least one of di(dioctyl pyrophosphate)hydroxyacetic acid titanate, dicarboxylic acyl ethylene diethylene titanate, triethanolamine titanate, and amide ethylene diethylene titanate.

[0010] By adopting the above technical solution, the titanate coupling agent molecule contains alkoxy and long-chain molecular units. When the coupling agent molecule acts on the B2O3-A12O3 multiphase powder, the alkoxy group captures the proton on the surface of the powder. The proton comes from the bound water in the powder, including crystal water, chemically adsorbed water and physically adsorbed water, thereby forming a chemical bond and covering the molecular layer of the coupling agent on the surface of the B2O3-A12O3 multiphase powder. The long-chain molecular structural unit in the coupling agent can be chemically cross-linked or physically entangled with the PET molecules, and finally the B2O3-A12O3 multiphase powder and the PET molecules are well combined, thereby improving the wear resistance of the material. In addition, the action of the titanate coupling agent reduces the surface energy of the powder, improves the dispersion ability of the powder in the resin, reduces the viscosity of the filling system, increases the filling amount, and reduces mechanical wear.

[0011] Preferably, the toughening agent is E-BA-GMA, and the GMA content in the toughening agent is 6-8%.

[0012] By adopting the above technical solution, the ethylene-butyl acrylate-glycidyl methacrylate block copolymer has good dispersibility and compatibility, which can change the internal stress distribution of the material, disperse the concentrated stress to a larger area, reduce local stress concentration, and thus improve the impact resistance of the PET material.

[0013] Preferably, the light stabilizer is at least one of 2,2,6,6-tetramethyl-4-piperidinyl stearate and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0014] By adopting the above technical solution, the light stabilizers are all free radical scavengers. When exposed to ultraviolet rays, the piperidine ring contained in its molecular structure is converted into a stable nitroxide free radical. After being exposed to ultraviolet rays, PET materials will produce alkyl free radicals, peroxyalkyl free radicals, etc. The appearance of these free radicals will accelerate the aging of PET materials. Nitrogen oxide free radicals will capture the free radicals generated by PET materials, generate corresponding esters or peroxy esters and other compounds, terminate the chain reaction, achieve the effect of light stabilization, and prevent the aging of PET materials.

[0015] Preferably, the antioxidant includes at least one of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate and diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0016] By adopting the above technical solution, the benzene ring in the antioxidant molecule carries a hydroxyl group, which can provide an efficient hydrogen donor, and the ortho or para position of the hydroxyl functional group has two tert-butyl substituent groups. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxy radicals, alkyl radicals or hydroxyl radicals, causing them to lose their original activity, reducing the source of free radicals, causing the oxidation reaction to terminate, thereby achieving an antioxidant effect and extending the service life of the PET material.

[0017] Preferably, the lubricant includes at least one of pentaerythritol stearate, solid paraffin, polyethylene wax, oxidized polyethylene wax, zinc stearate, calcium stearate, and fatty amide.

[0018] By adopting the above technical scheme, the lubricant molecular structure generally has two parts: a non-polar long chain and a polar group, which plays a role in reducing the intermolecular cohesion in the melting system of the matrix resin, thereby reducing the internal friction of the plastic melt, increasing the melting rate and melt deformability of the plastic, reducing the melt viscosity and improving the plasticizing properties.

[0019] In the second aspect, the present application provides a process for preparing a wear-resistant PET bottle, which adopts the following technical solution: A method for preparing a wear-resistant PET bottle comprises the following steps: The raw materials are weighed according to the component ratio, and the PET resin, modified ceramic powder, toughening agent, antioxidant, light stabilizer and lubricant are stirred and mixed, and then placed in an extruder, and then glass fiber is added, mixed evenly, and melt-extruded at 170-190°C. After granulation, the PET material is obtained, and then the PET material is heated to 210-220°C to form a melt, and a bottle embryo is injection molded, and finally the bottle embryo is stretched and blow-molded into a bottle body to obtain a wear-resistant PET bottle.

[0020] By adopting the above technical solution, the wear resistance of PET bottles is significantly improved by adding modified ceramic powder and glass fiber, making them more durable during use and reducing the risk of wear and damage. The addition of glass fiber enhances the mechanical strength of PET materials, allowing the finished bottles to withstand greater pressure and impact. The use of antioxidants and light stabilizers improves the thermal stability and light resistance of PET materials and extends the service life of bottles, especially in high temperature or direct sunlight environments. The addition of toughening agents and lubricants improves the processing properties of PET materials, making them smoother during extrusion, injection molding and blow molding, reducing energy consumption and material loss during production.

[0021] Preferably, the preparation method of the modified ceramic powder is: ① Place the B2O3-A12O3 composite powder in a NaOH solution, stir at 50-60°C for 3-4h, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain a pretreated B2O3-A12O3 composite powder; ② Add the titanate coupling agent to the ethanol solution, adjust the pH to 6.5-7.5, stir and hydrolyze for 1-2 hours to obtain a hydrolysis coupling agent solution, then add the pretreated B2O3-A12O3 composite powder to the hydrolysis coupling agent solution, stir at 50-60°C for 2-3 hours, ultrasonically disperse for 30-40 minutes, filter and separate after the reaction is completed, wash with acetone 2-3 times, and dry at 40-50°C for 2-4 hours to obtain a modified ceramic powder.

[0022] By adopting the above technical solution, the B2O3-A12O3 composite powder is pretreated to increase the content of surface hydroxyl groups. The hydrolysis of the titanate coupling agent can form an active layer on the surface of the powder, which helps to improve the bonding force between the powder and the PET resin. The ultrasonic dispersion step helps to evenly disperse the powder in the PET resin, avoid agglomeration, and ensure the uniformity and consistency of the composite material.

[0023] Preferably, the preparation method of the B2O3-A12O3 composite powder is: Add micron boron oxide and nano aluminum oxide to ethanol, mix well, and perform ball grinding for 50-70 minutes, followed by ultrasonication, filtration, and drying to obtain B2O3-A12O3 composite phase powder.

[0024] By adopting the above technical scheme, the ball milling method has a certain promoting effect on the particle dispersion. The boron oxide particles are dispersed with each other. At the same time, there are many aluminum oxide particles around the boron oxide particles. The boron oxide and aluminum oxide particles are in contact with each other, so that the B2O3-A12O3 complex phase powders are well dispersed without obvious agglomeration.

[0025] In summary, this application at least includes the following beneficial technical effects: In this application, PET resin is used as the matrix resin, and the ceramic powder is modified by a titanate coupling agent. One end of the coupling agent molecule is connected to the B2O3-A12O3 composite powder particles by chemical action, and the other end is cross-linked with the PET resin to increase the compatibility of the ceramic powder with the matrix resin, so that the ceramic powder is uniformly filled with the PET resin. Since the B2O3-A12O3 composite powder is small in size, it can be evenly dispersed in the matrix resin. During the friction process, on the one hand, the powder particles that are debonded when the material surface is worn have strong surface activity and are easy to combine with the dual surface to form a fine thin layer, thereby forming a boundary lubrication film on the friction surface. On the other hand, it can produce enrichment on the polymer wear surface, and the amount of powder particles re-embedded in the polymer matrix almost reaches the extent of covering the entire wear surface, forming a complete lubrication film on the polymer surface, so that the possibility of direct wear of the PET resin matrix is ​​reduced, thereby improving the overall wear resistance of the material. In addition, the addition of glass fiber can further improve the crystallization performance and mechanical properties of the PET material. DETAILED DESCRIPTION

[0026] Preparation Example Preparation Example 1 The preparation method of the modified ceramic powder is as follows: ① Add 2kg of micron boron oxide and 3.6kg of nano-alumina into ethanol, mix well, and perform ball grinding for 50 minutes, followed by ultrasonication, filtration, and drying to obtain B2O3-A12O3 composite powder; ② Place 4 kg of B2O3-A12O3 composite powder in a NaOH solution, stir at 50°C for 3 h, then wash with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry to obtain pretreated B2O3-A12O3 composite powder; ③ Add 0.2 kg of di(dioctyl pyrophosphate)hydroxyacetic acid titanate to the ethanol solution, adjust the pH to 6.5, stir and hydrolyze for 1 hour to obtain a hydrolysis coupling agent solution, then add the pretreated B2O3-A12O3 composite powder to the hydrolysis coupling agent solution, stir at 50°C for 2 hours, ultrasonically disperse for 30 minutes, and after the reaction is completed, filter and separate, wash twice with acetone, and dry at 40°C for 2 hours to obtain a modified ceramic powder.

[0027] Preparation Example 2 The preparation method of the modified ceramic powder is as follows: ① Add 3kg of micron boron oxide and 6kg of nano-alumina into ethanol, mix well, and perform ball grinding for 60 minutes, followed by ultrasonication, filtration, and drying to obtain B2O3-A12O3 composite powder; ② Place 6kg of B2O3-A12O3 composite powder in a NaOH solution, stir at 55°C for 3.5h, then wash it alternately with deionized water and alcohol for 3 times, filter it under reduced pressure to remove excess water, and dry it to obtain a pretreated B2O3-A12O3 composite powder; ③ Add 0.36kg of dicarboxylic acyl ethylene dititanate to an ethanol solution, adjust the pH to 7.0, stir and hydrolyze for 2h to obtain a hydrolysis coupling agent solution, then add the pretreated B2O3-A12O3 composite powder to the hydrolysis coupling agent solution, stir at 55°C for 2.5h, ultrasonically disperse for 35min, filter and separate it after the reaction is completed, wash it with acetone 3 times, and dry it at 45°C for 3h to obtain a modified ceramic powder.

[0028] Preparation Example 3 The preparation method of the modified ceramic powder is as follows: ① Add 4kg of micron boron oxide and 8.8kg of nano-alumina into ethanol, mix well, and perform ball grinding for 70 minutes, followed by ultrasonication, filtration, and drying to obtain B2O3-A12O3 composite powder; ② Place 8kg of B2O3-A12O3 composite powder in a NaOH solution, stir at 60°C for 4h, then wash with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry to obtain pretreated B2O3-A12O3 composite powder; ③ Add 0.56 kg of triethanolamine titanate to the ethanol solution, adjust the pH to 7.5, stir and hydrolyze for 2 hours to obtain a hydrolysis coupling agent solution, then add the pretreated B2O3-A12O3 composite powder to the hydrolysis coupling agent solution, stir at 60°C for 3 hours, ultrasonically disperse for 40 minutes, filter and separate after the reaction is completed, wash with acetone 3 times, and dry at 50°C for 4 hours to obtain a modified ceramic powder. Example

[0029] Example 1 A wear-resistant PET bottle, comprising the following raw materials: 60kg PET resin (DuPont FG530 NC011), 4kg modified ceramic powder (prepared in Preparation Example 1), 8kg glass fiber, 1kg E-MA-GMA (GMA content is 6%), 0.1kg tetrakis (3,5-di-tert-butyl-4-hydroxy) benzene propionate pentaerythritol ester, 0.3kg 2,2,6,6-tetramethyl-4-piperidinyl stearate, 0.2kg solid paraffin, 0.2kg pentaerythritol stearate.

[0030] The preparation process of the wear-resistant PET bottle of the first embodiment includes the following steps: The raw materials are weighed according to the component ratio, PET resin, modified ceramic powder, E-MA-GMA, pentaerythritol tetra(3,5-di-tert-butyl-4-hydroxy)benzene propionate, 2,2,6,6-tetramethyl-4-piperidinyl stearate, solid paraffin and pentaerythritol stearate are stirred and mixed, and then placed in an extruder, and then glass fiber is added and mixed evenly, and melt-extruded at 170° C. and granulated to obtain PET material, and then the PET material is heated to 210° C. to form a melt, and a bottle embryo is injection molded, and finally the bottle embryo is stretched and blow-molded into a bottle body to obtain a wear-resistant PET bottle.

[0031] Example 2 A wear-resistant PET bottle, comprising the following raw materials: 65kg PET resin (DuPont FG530 NC011), 6kg modified ceramic powder (prepared in Preparation Example 1), 10kg glass fiber, 2kg E-MA-GMA (GMA content is 7%), 0.2kg thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.4kg bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, 0.2kg zinc stearate, and 0.2kg calcium stearate.

[0032] The preparation process of the wear-resistant PET bottle of the second embodiment includes the following steps: The raw materials are weighed according to the component ratio, and the PET resin, modified ceramic powder, E-MA-GMA, diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, zinc stearate and calcium stearate are stirred and mixed, and then placed in an extruder, and then glass fiber is added and mixed evenly, and melt-extruded at 180°C. After granulation, a PET material is obtained, and then the PET material is heated to 215°C to form a melt, and a bottle embryo is injection molded, and finally the bottle embryo is stretched and blow-molded into a bottle body to obtain a wear-resistant PET bottle.

[0033] Example 3 A wear-resistant PET bottle, comprising the following raw materials: 70kg PET resin (DuPont FG530 NC011), 8kg modified ceramic powder (prepared in Preparation Example 1), 12kg glass fiber, 3kg E-MA-GMA (GMA content is 8%), 0.3kg pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)benzenepropionate, 0.5kg bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 0.2kg oxidized polyethylene wax, and 0.2kg fatty amide.

[0034] The preparation process of the wear-resistant PET bottle of the third embodiment includes the following steps: The raw materials are weighed according to the component ratio, and the PET resin, modified ceramic powder, E-MA-GMA, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)benzene propionate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, oxidized polyethylene wax and fatty amide are stirred and mixed, and then placed in an extruder, and then glass fiber is added and mixed evenly, and melt-extruded at 190° C. and granulated to obtain a PET material, and then the PET material is heated to 220° C. to form a melt, and a bottle embryo is injection molded, and finally the bottle embryo is stretched and blow-molded into a bottle body to obtain a wear-resistant PET bottle.

[0035] Example 4 The difference between this embodiment and embodiment 2 is that the modified ceramic powder adopts the modified ceramic powder prepared in preparation example 2 in an equal amount.

[0036] Example 5 The difference between this embodiment and embodiment 2 is that the modified ceramic powder adopts the modified ceramic powder prepared in preparation example 3 in an equal amount.

[0037] Comparative Example Comparative Example 1 A wear-resistant PET bottle, which differs from Example 2 in that the modified ceramic powder is replaced by an equal amount of B2O3-A12O3 composite phase powder.

[0038] Comparative Example 2 A wear-resistant PET bottle, which is different from Example 2 in that the B2O3-A12O3 composite powder in the raw material for preparing the modified ceramic powder is replaced by an equal amount of micron boron oxide.

[0039] Comparative Example 3 A wear-resistant PET bottle, which is different from Example 2 in that the B2O3-A12O3 complex phase powder in the raw material for preparing the modified ceramic powder is replaced by an equal amount of nano-alumina.

[0040] Comparative Example 4 A wear-resistant PET bottle, which differs from Example 2 in that the modified ceramic powder is replaced by an equal amount of glass fiber.

[0041] Performance testing 1. Wear resistance test: The friction and wear test was conducted using a MM-200 friction and wear tester. The sample size was 6mm×7mm×30mm. Before each test, the friction surface and the mating part of the sample were polished smooth with 1200# water-abrasive sandpaper, with a roughness of about Ra=0.4μm, and cleaned with acetone. The friction mating part was 45# steel, the mating wheel radius was 20mm, the hardness was HRC42-45, the load was 98N, the linear speed was 0.42m / s, and the dry friction was 2h. Table 1 shows the test results.

[0042] Determination of friction coefficient: During the friction and wear test, the friction torque of the material wear can be directly read from the MM-200 friction and wear tester. The friction coefficient is calculated from the friction torque using formula (1). The average value of three repeated experiments is taken as the final result.

[0043] μ=T / (RP)(1) Where T is the friction torque, R is the diameter of the steel wheel (40mm), and P is the load.

[0044] Determination of wear mass loss: Before and after the wear test, the mass of the PET composite material was weighed with an electronic balance with a sensitivity of 0.1 mg, the wear mass loss was calculated, and the average value of three repeated tests was taken as the final result.

[0045] 2. Impact resistance test: The impact test is carried out according to GB / T 1043.1-2008. The impact test is carried out on the impact test specimens made by injection molding on the XJ-300A impact test machine. The specimens are standard specimens with a cross-sectional size of 1.5cm×0.7cm. The notch type is C-type, the notch width is 2mm, and the notch depth is 3mm. Table 1 shows the test results.

[0046] 3. Tensile performance test: The tensile test is carried out in accordance with GB / T 1040.2-2022. The tensile test specimens made by injection molding are subjected to tensile tests on a CMT5105 SANS microcomputer-controlled electronic universal tensile testing machine. The specimen is dumbbell-shaped, with a gauge length of 8 cm, a width of 0.7 cm, and a thickness of 0.2 cm. The test results are shown in Table 1.

[0047] Table 1 According to the comparison between Example 2 and Comparative Example 1 and the data in Table 1, it can be seen that when the ceramic powder is directly added to the raw material without modification, the powder cannot be well combined with the matrix resin due to the poor compatibility with the matrix resin, so the improvement of the wear resistance of the PET material is not obvious. However, the modification of the surface of the ceramic powder can effectively improve the dispersion performance of the B2O3-A12O3 complex phase powder in the PET matrix resin, which is beneficial to improve the wear resistance of the PET bottle.

[0048] According to the comparison between Example 2 and Comparative Example 2 and the data in Table 1, it can be seen that the use of a single-phase powder filled in the matrix resin does not improve the wear resistance of the material ideally. The reason may be that due to the inertness of the chemical reaction of boron oxide, it cannot combine with the functional groups in the titanate coupling agent, and the micron-sized boron oxide particles fall off and remain on the friction interface, which easily causes serious abrasive wear. By combining micron boron oxide and nano-alumina to prepare B2O3-A12O3 multiphase powder, Nano-alumina plays a small size effect. When the material surface is worn, the debonded nano-alumina has strong surface activity and is easy to combine with the pair to form a fine thin layer, thereby slowing down the wear of the PET material and improving the wear resistance of the material. In addition, since the alumina particles absorb the impact energy, they effectively delay and prevent the destruction of the PET material, producing a toughening effect.

[0049] According to the comparison between Example 2 and Comparative Example 3 and the data in Table 1, it can be seen that the use of nano-alumina powder alone to fill the matrix resin does not improve the wear resistance of the material ideally. The reason may be that the interface of the nano-alumina particles is fuzzy, there is a serious agglomeration phenomenon, and it is not easy to disperse in the high-viscosity matrix resin melt system. By combining micron boron oxide and nano-alumina to prepare B2O3-A12O3 composite powder, the nano-alumina is relatively evenly dispersed around the micron boron oxide particles, rather than in a clumping state, and the agglomeration phenomenon is not obvious. The nano-alumina forms a certain bonding and coating effect on the micron boron oxide, so that the composite ceramic powder has a good phase, thereby achieving the purpose of improving the wear resistance of PET. In addition, because the alumina particles absorb the impact energy, they effectively delay and prevent the destruction of the PET material, producing a toughening effect.

[0050] According to the comparison between Example 2 and Comparative Example 4 and the data in Table 1, it can be seen that when the modified ceramic powder is not added, the wear resistance of the PET resin is poor. On the contrary, after the modified ceramic powder is added, the powder particles that are debonded when the material surface is worn have strong surface activity and are easy to combine with the dual surface to form a fine thin layer, thereby forming a boundary lubrication film on the friction surface, reducing the possibility of direct wear of the PET resin matrix, thereby improving the overall wear resistance of the material.

[0051] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wear-resistant PET bottle, characterized in that: The invention is prepared from the following raw materials by weight: PET resin 60-70 parts; 4-8 parts of modified ceramic powder; Glass fiber 8-12 parts; 1-3 parts of toughening agent; Antioxidant 0.1-0.3 parts; Light stabilizer 0.3-0.5 parts; Lubricant 0.4-0.6 parts; The modified ceramic powder is prepared from B2O3-A12O3 composite powder and a titanate coupling agent, and the weight ratio of the B2O3-A12O3 composite powder to the titanate coupling agent is 10:(0.5-0.7).

2. A wear-resistant PET bottle according to claim 1, characterized in that: The B2O3-A12O3 composite powder is prepared from micron boron oxide and nano alumina, and the weight ratio of the micron boron oxide to the nano alumina is 1:(1.8-2.2).

3. A wear-resistant PET bottle according to claim 1, characterized in that: The titanate coupling agent includes at least one of di(dioctyl pyrophosphate)hydroxyacetic acid titanate, dicarboxylic acyl ethylene diethylene titanate, triethanolamine titanate, and amide ethylene diethylene titanate.

4. A wear-resistant PET bottle according to claim 1, characterized in that: The toughening agent is E-BA-GMA, and the GMA content in the toughening agent is 6-8%.

5. A wear-resistant PET bottle according to claim 1, characterized in that: The light stabilizer is at least one of 2,2,6,6-tetramethyl-4-piperidinyl stearate and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

6. A wear-resistant PET bottle according to claim 1, characterized in that: The antioxidant includes at least one of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate and diethylene sulfide bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

7. The wear-resistant PET bottle according to claim 1, characterized in that: The lubricant includes at least one of pentaerythritol stearate, solid paraffin, polyethylene wax, oxidized polyethylene wax, zinc stearate, calcium stearate, and fatty amide.

8. A process for preparing a wear-resistant PET bottle according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials are weighed according to the component ratio, and the PET resin, modified ceramic powder, toughening agent, antioxidant, light stabilizer and lubricant are stirred and mixed, and then placed in an extruder, and then glass fiber is added, mixed evenly, and melt-extruded at 170-190°C. After granulation, the PET material is obtained, and then the PET material is heated to 210-220°C to form a melt, and a bottle embryo is injection molded, and finally the bottle embryo is stretched and blow-molded into a bottle body to obtain a wear-resistant PET bottle.

9. A process for preparing a wear-resistant PET bottle according to any one of claim 8, characterized in that: The preparation method of the modified ceramic powder is: ① Place the B2O3-A12O3 composite powder in a NaOH solution, stir at 50-60°C for 3-4h, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain a pretreated B2O3-A12O3 composite powder; ② Add the titanate coupling agent to the ethanol solution, adjust the pH to 6.5-7.5, stir and hydrolyze for 1-2 hours to obtain a hydrolysis coupling agent solution, then add the pretreated B2O3-A12O3 composite powder to the hydrolysis coupling agent solution, stir at 50-60°C for 2-3 hours, ultrasonically disperse for 30-40 minutes, filter and separate after the reaction is completed, wash with acetone 2-3 times, and dry at 40-50°C for 2-4 hours to obtain a modified ceramic powder.

10. A process for preparing a wear-resistant PET bottle according to any one of claim 9, characterized in that: The preparation method of the B2O3-A12O3 composite powder is as follows: Add micron boron oxide and nano alumina into ethanol, mix well, and perform ball grinding for 50-70 minutes, followed by ultrasonication, filtration, and drying to obtain B2O3-A12O3 composite powder.

Citation Information

Patent Citations

  • Surface-modified metal boride / Al2O3 multiphase ceramic powder and preparation method thereof

    CN103160148A

  • Preparation method of scratching-resistant polypropylene composite material

    CN108727702A

  • High-strength wear-resistant PET material and preparation method thereof

    CN118256071A

Cited By

  • Composite material and application thereof in preparation of high-transparency colorful color-changing anti-counterfeiting film

    CN121736456A

  • Food-grade beverage bottle material and preparation method thereof

    CN122037496A

  • A food-grade beverage bottle material and its preparation method

    CN122037496B